Effectiveness of Booster Measles-Mumps-Rubella Vaccination in Lower COVID-19 Infection Rates: A Retrospective Cohort Study in Turkish Adults - Yengil E; Onlen Y; Ozer C; Hambolat M; Ozdogan M (International Journal of General Medicine, 2021)
Erhan Yengil,1 Yusuf Onlen,2 Cahit Ozer,1 Mustafa Hambolat,3 Mehmet Ozdogan4 1Department of Family Medicine, Hatay Mustafa Kemal University School of Medicine, Hatay, Turkey; 2Department of Infectious Disease and Clinical Microbiology, Hatay Mustafa Kemal University School of Medicine, Hatay, Turkey; 3Province Health Manager of Hatay, Turkey; 4Head of Provincial Public Health Department, Hatay, TurkeyCorrespondence: Erhan YengilHatay Mustafa Kemal University, Faculty of Medicine, Department of Family Medicine, Hatay, TurkeyEmail dryengil@yahoo.comObjective: The aim of this study was to investigate the effectiveness of booster vaccination of adults with measles-mumps-rubella in the COVID-19 infection rates.Methods: In order to investigate this hypothesis, we tested COVID-19 positivity rate through PCR assay on the participants (n=245; male), who had to share the same student accommodation together with the same dining hall to provide governmental service. Participants were divided into two groups based on their booster vaccination status with measles-mumps-rubella: the non-vaccinated group (n=207) and the vaccinated group (n=38). The rate of COVID-19 seropositivity, age, body mass index (BMI), active smoking and presence of comorbidity were also measured and recorded.Results: All of the participants were healthy, and age distribution, comorbidity rates, active smoking status and BMI did not vary significantly among the two groups (p=0.305, p=0.594, p=0.280, and p=0.922, respectively). About 36.7% (n=90) of the participants were found to be COVID-19 positive by PCR among which the non-vaccinated cases had higher rates of COVID-19 seropositivity than the vaccinated cases (40.6% vs 15.8%) (OR=3.6, 95%CI: 1.5– 9.0, p=0.004).Conclusion: Based on these results, we cautiously predict that immunity produced by MMR vaccination boosters may provide some degree of protection against COVID-19 in the adult population.Keywords: COVID-19, live attenuated vaccines, booster vaccination, MMR